1995
DOI: 10.1128/iai.63.1.248-252.1995
|View full text |Cite
|
Sign up to set email alerts
|

Diminished priming of neonatal polymorphonuclear leukocytes by lipopolysaccharide is associated with reduced CD14 expression

Abstract: Previous research in our laboratory has shown that polymorphonuclear leukocytes (PMN) from neonates are not primed effectively in vitro with lipopolysaccharide (LPS) (from Escherichia coli O111:B4) compared with priming of adult PMN. This finding led us to speculate that differences between neonatal and adult LPS receptors may account for the lower response by neonatal PMN to LPS. In these experiments, we investigated if CD14 or other LPS receptors contribute to the priming activity of PMN by LPS. We found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
9
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 23 publications
4
9
0
Order By: Relevance
“…We have identified significant agespecific differences in the LPS activation of a major intracellular MAP kinase, p38, and have shown that newborn PMN have lower concentrations of MyD88, an important mediator of LPS signaling. In this and previous studies 10 we have shown no differences between adult and newborn PMN in the levels of the major LPS membrane receptors (CD14 and TLR-4). Moreover, many of the intracellular kinases implicated in LPS signaling (Erk, p38, Lyn, Hck, Fgr) are present in similar amounts in these cells.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…We have identified significant agespecific differences in the LPS activation of a major intracellular MAP kinase, p38, and have shown that newborn PMN have lower concentrations of MyD88, an important mediator of LPS signaling. In this and previous studies 10 we have shown no differences between adult and newborn PMN in the levels of the major LPS membrane receptors (CD14 and TLR-4). Moreover, many of the intracellular kinases implicated in LPS signaling (Erk, p38, Lyn, Hck, Fgr) are present in similar amounts in these cells.…”
Section: Discussionsupporting
confidence: 54%
“…34 Indeed, our findings of diminished LPS responses of newborn PMN are similar to those using cells from MyD88 -/mice or MyD88 truncated cells. 10 In such cells LPS-induced nitric oxide release and degranulation are diminished although responses to other stimuli are preserved. 30,[35][36][37] The increased susceptibility of human newborns to gram-negative bacterial infections is due to a variety of humoral and cellular factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possibility is that there is a shift in the composition of circulating monocyte populations and that these differ between mothers of term infants and mothers of VLBW infants. A recent study has shown diminished expression of CD14 on neonatal monocytes and neutrophils (35). Furthermore, the expression of these receptors may be altered by steroid, endocrine, or other serumderived factors in mothers of VLBW infants.…”
Section: Discussionmentioning
confidence: 99%
“…Once at the site of infection, neutrophils of infants do not function at the same level as those of adults (187). They have about half the amount of lactoferrin, a 30% reduction in bactericidial/permeability increasing protein (BPI), and impaired oxidase activity (188)(189)(190).…”
Section: Differences Between Infant and Adult Lungmentioning
confidence: 99%